Perspectives of COPD patients, publicly funded scientists, and industry representatives on responsibility and stakeholder engagement in drug discovery research - Zainab Afshan Sheikh; Helen Yu (Journal of Responsible Innovation)
Ensuring societal influence in research and innovation through stakeholder engagement is vital in the Responsible Research and Innovation (RRI) framework. By studying a drug discovery project, we examine how stakeholders can influence drug discovery and development meaningfully. Through semi-structured interviews, we explore: How do patients as potential users of a new drug, the scientists who discover it, and the industry that might develop it, think about responsibility and stakeholder engagement in drug discovery? Most of the responses voiced by our informants about responsibility and stakeholder engagement relate to the broader institutional and political context of health-related innovation, rather than the specific research project. We argue, that in order to make stakeholder engagement work within some forms of drug discovery research, it should be used as a forum for mobilizing political and organizational debate, taking critical dialogues beyond project-specific engagement in innovation.